2019
DOI: 10.1186/s12957-019-1733-2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical invasion, lymphovascular space invasion, and ovarian metastasis as predictors of lymph node metastasis and poor outcome on stages I to III endometrial cancers: a single-center retrospective study

Abstract: BackgroundThe aim of this study is to determine pathological factors that increase the risk of LNM and indicate poor survival of patients diagnosed with endometrial cancer and treated with surgical staging.MethodBetween January 2010 and November 2018, we enrolled 874 eligible patients who received staging surgery in the First Affiliated Hospital of Anhui Medical University. The roles of prognostic risk factors, such as age, histological subtype, tumor grade, myometrial infiltration, tumor diameter, cervical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…The pooled result showed that tumor size >20 mm was correlated with high LNM, and the pooled OR was 3.69 (95% CI [2.97, 4.60], p < 0.001), with heterogeneity (I 2 = 0%, p = 0.85). A total of 28,434 patients had FIGO stage III–IV endometrial cancer, based on 21 studies that were enrolled in our meta-analysis ( 15 , 16 , 18 20 , 22 26 , 28 , 29 , 32 36 , 38 40 , 45 ). The pooled result showed that tumor size >20 mm was correlated with high LNM, and the pooled OR was 4.32 (95% CI [3.71, 5.03], p < 0.001), with heterogeneity (I 2 = 0%, p = 0.58) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled result showed that tumor size >20 mm was correlated with high LNM, and the pooled OR was 3.69 (95% CI [2.97, 4.60], p < 0.001), with heterogeneity (I 2 = 0%, p = 0.85). A total of 28,434 patients had FIGO stage III–IV endometrial cancer, based on 21 studies that were enrolled in our meta-analysis ( 15 , 16 , 18 20 , 22 26 , 28 , 29 , 32 36 , 38 40 , 45 ). The pooled result showed that tumor size >20 mm was correlated with high LNM, and the pooled OR was 4.32 (95% CI [3.71, 5.03], p < 0.001), with heterogeneity (I 2 = 0%, p = 0.58) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Li et al reported that lymphovascular space invasion was a poor survival risk factor, but this study noted lymphovascular space invasion in multiple stages of endometrial cancer. 15 Cusano et al reported a higher mortality rate in lymphovascular space invasionpositive cases. However, this study only analyzed stage I endometrial cancer cases as a whole, rather than classifying patients into stages IA and IB.…”
Section: Discussionmentioning
confidence: 96%
“…The requirement for lymph node dissection was designed according to Mayo criteria; It has been determined that lymph node dissection is not required in cases of ≤ 2 cm tumor size (TD), <1/2 myometrial invasion (MI), and low-grade tumors (12). Otherwise, patients with adequate lymph dissection were included in the study, and it was decided to remove at least 15 pelvic and/or paraaortic lymph nodes for adequate lymph dissection (13,14). All patients were re-evaluated in the gynecologic oncology council before anesthesia examination.…”
Section: Methodsmentioning
confidence: 99%